1972
DOI: 10.1111/j.1476-5381.1972.tb08096.x
|View full text |Cite
|
Sign up to set email alerts
|

A neuronal basis for the alerting action of (+)‐amphetamine

Abstract: Summary1. (+ )-Amphetamine mimicked the excitatory and inhibitory actions of (-)-noradrenaline on single neurones in the brain stem of acute halothaneanaesthetized rats when these compounds were applied by iontophoresis.(+)-Amphetamine had no actions on neurones unaffected by (-)-noradrenaline.2. These mimicking actions of (+ )-amphetamine could not be observed 20 h after treatment of the animals with reserpine 5 mg/kg. 3. The enzyme inhibitors a-methyl-p-tyrosine and FLA 63 also greatly reduced the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…The actions of iontophoretically applied (-)noradrenaline on these neurones were qualitatively similar to those described in previous reports of its effects in the cat and rat (Boakes, Bradley, Brookes, Candy & Wolstencroft, 1971;Boakes et al, 1972) (Figure la) or smaller in amplitude than that to noradrenaline, despite the fact that (+ )amphetamine was usually applied for a longer time. The latency of the excitatory response to (+)-amphetamine was usually similar to that for noradrenaline (Figure la).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The actions of iontophoretically applied (-)noradrenaline on these neurones were qualitatively similar to those described in previous reports of its effects in the cat and rat (Boakes, Bradley, Brookes, Candy & Wolstencroft, 1971;Boakes et al, 1972) (Figure la) or smaller in amplitude than that to noradrenaline, despite the fact that (+ )amphetamine was usually applied for a longer time. The latency of the excitatory response to (+)-amphetamine was usually similar to that for noradrenaline (Figure la).…”
Section: Resultssupporting
confidence: 73%
“…Rossum, Schoot & Hurkmans (1962) suggested that amphetamine acts directly on catecholamine receptors and iontophoretic studies in the cerebellar cortex, hippocampus and caudate nucleus have supported this (Hoffer, Siggins & Bloom, 1971;Feltz & de Champlain, 1972;Segal & Bloom, 1974). However, an indirect mechanism of amphetamine action involving release of endogenous catecholamines has also been proposed (Weissman, Koe & Tenen, 1966) and experiments in this laboratory (Boakes, Bradley & Candy, 1972) demonstrated that the effects of iontophoretically applied (+ )amphetamine on neurones in the brain stem of anaesthetized rats were dependent on the presence of endogenous noradrenaline. It has been suggested that amphetamine produces electrocortical desynchrony and behavioural alerting by an action on the reticular formation of the brain stem Bradley & Elkes, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that amphetamine is capable of mimicking both the inhibitory and excitatory actions of NA on single neurones in the brain stem of rats when these compounds are applied by iontophoresis (Straschill & Perwein, 1971; Boakes, Bradley & Candy, 1972). Moreover, certain of the peripheral and central actions of chlorpromazine (CPZ) have also been ascribed to postsynaptic effects at noradrenergic synapses (Bradley, Wolstencroft, Hosli & Avanzino, 1966;Gordon, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of amphetamine on noradrenergic transmission has been related at the neuronal level to the induced release of NA, NA reuptake blockade, monoamine oxidase (MAO) inhibition, as well as a direct effect on postsynaptic receptors (Blaschko, Richter & Schlossman, 1937, Rossum, Schoot & Hurkmans, 1962Glowinski & Axelrod, 1965;Boakes et al, 1972;Segal & Bloom, 1974). In an attempt to determine the nature of the amphetamine effect within the DRN and to distinguish between the pre-and postsynaptic actions of amphetamine, a comparison has been made with the effects of the NA reuptake blocker, desmethylimipramine.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of amantadine were compared with responses to dopamine itself and to amphetamine, which is thought to stimulate central catecholamine receptors indirectly by releasing the amines from neuronal storage sites (Moore, 1963;Carlsson, Lindqvist, Dahlstrom, Fuxe & Masuoka, 1965;Carlsson, Lindqvist, Fuxe & Hamberger, 1966; Christie & Crow, 1971;Boakes, Bradley & Candy, 1972). Chlorpromazine was used as a dopamine receptor blocking agent (van Rossum, 1966;York, 1972) to examine the specificity of amantadine's effects on dopamine receptors.…”
Section: Introductionmentioning
confidence: 99%